2014
DOI: 10.1093/nar/gku236
|View full text |Cite
|
Sign up to set email alerts
|

AMPK regulates histone H2B O-GlcNAcylation

Abstract: Histone H2B O-GlcNAcylation is an important post-translational modification of chromatin during gene transcription. However, how this epigenetic modification is regulated remains unclear. Here we found that the energy-sensing adenosine-monophosphate-activated protein kinase (AMPK) could suppress histone H2B O-GlcNAcylation. AMPK directly phosphorylates O-linked β-N-acetylglucosamine (O-GlcNAc) transferase (OGT). Although this phosphorylation does not regulate the enzymatic activity of OGT, it inhibits OGT–chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 47 publications
3
92
0
3
Order By: Relevance
“…It is noteworthy that UDP-GlcNAc is the second most abundant nucleotide in the cell after ATP. O-GlcNAcylation of H2B at serine 112 has been associated with active gene transcription during times of positive energy balance 66 . However, the impact of these mechanisms on transcriptional regulation in the context of energy homeostasis remains largely uncharted.…”
Section: Histone Variantmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that UDP-GlcNAc is the second most abundant nucleotide in the cell after ATP. O-GlcNAcylation of H2B at serine 112 has been associated with active gene transcription during times of positive energy balance 66 . However, the impact of these mechanisms on transcriptional regulation in the context of energy homeostasis remains largely uncharted.…”
Section: Histone Variantmentioning
confidence: 99%
“…In a recent study, AMP-activated protein kinase (AMPK) was shown to reduce histone H2B O-GlcNAcylation by phosphorylation of O-GlcNAc transferase (OGT). AMPK is also O-GlcNAcylated itself, creating a regulatory feedback loop between OGT and AMPK 66 . AMPK was also shown to associate directly with chromatin at p53-binding sites, leading to phosphorylation of H2B at serine 36 and regulation of p53-dependent genes such as Cdkn1a (which encodes p21), Cpt1c (carnitine palmitoyltransferase 1C), Rprm (reprimo) and cyclin G 68 .…”
Section: Histone Variantmentioning
confidence: 99%
“…14,15,31,33 Upon further characterization, it was reported that histone H2B S112 O-GlcNAcylation promotes H2B monoubiquitination on lysine 120 (H2B K120ub), an event associated with transcriptional activation. 33,34 On the other hand, histone H3 serine 10 was also reported to be O-GlcNAcylated, and this appears to compete with the phosphorylation of this site as well as modulate the transcriptional state of chromatin. 14,15 Other O-GlcNAcylation sites were reported within the globular domains of histones suggesting that they may function in maintaining higher-order chromatin structure.…”
Section: Undetectable Histone O-glcnacylation In Mammalian Cellsmentioning
confidence: 99%
“…32,35 To further investigate the potential biological significance of histone OGlcNAcylation, we initially sought to reproduce previously published results on the modification of histones H2B and H2A. 14,30,[32][33][34] We co-expressed Flag-H2B or Flag-H2A with either Myc-OGT or the D925A catalytic inactive mutant (Myc-OGT CD). 36 Co-expression of Myc-TET2 with Myc-OGT was also included, since their association was expected to significantly increase OGT-mediated histone OGlcNAcylation.…”
Section: Histone O-glcnacylation Was Undetectable Using Various Extramentioning
confidence: 99%
“…Recent studies have also shown an important role of AMPK in O-GlcNAcylation of H2B. Xu et al found that AMPK can phosphorylate OGT at Thr444 and that this phosphorylation blocks OGT recruitment to chromatin and suppress histone O-GlcNAcylation [23]. However, under high nutrition conditions, the AMPK is inactivated and OGT can bind and modify H2B.…”
Section: Histone H2b Modificationsmentioning
confidence: 99%